Budidaya tanaman hidroponik melalui pendampingan pemanfaatan limbah anorganik sebagai media tanam di sekolah - Fatmawati, Baiq; Ariandani, Nunung; Muliawan, Wawan; Fajri, Nurul; Sarwati, Sarwati; Marzuki, M.; Wazni, M. Khairul (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Hydroponic farming has emerged as an effective alternative to overcome land limitations, especially in urban and compact residential areas. Focusing on two Madrasah Aliyah in East Lombok, the Community Service Program by the Biology Education Department of Universitas Hamzanwadi implemented hydroponic techniques as an innovative farming method. This initiative aimed to enhance environmental awareness and farming skills among students, while utilizing styrofoam waste as a planting medium. The process included socialization, seedling production, planting, maintenance, and harvesting, using plants such as water spinach, lettuce, and spinach. The implementation method incorporated Participatory Rural Appraisal (PRA), enabling active participation from students and teachers. The program was conducted from March to November 2023 at MA NWDI Juet and MA Ridlol Walidain NW Batu Bangka - Jenggik. The mentoring process involved various stages, from introducing hydroponic techniques to creating planting media and planting, including the use of AB Mix nutrients and rockwool as planting media. The results of the activity showed successful cultivation of hydroponic water spinach, while lettuce and spinach experienced crop failure. The primary causes of this failure were inadequate care, light, and temperature. Nevertheless, the activity successfully educated students on the importance of hydroponic agriculture and creative waste utilization, providing new insights into urban farming. In conclusion, the hydroponic approach can be an efficient solution for cultivating plants in limited spaces, offering educational and environmental benefits. This program also highlighted the potential of styrofoam waste as a hydroponic planting medium, underscoring the importance of waste utilization for environmental sustainability.